Instrument for evaluation and training of decision making in dual tasks in soccer: validation and application - Souza, L. R. O. d.; Rezende, A. L. G. d.; Carmo, J. d. (Sensors, 2024)
Training in team sports such as soccer requires advanced technical and tactical skills for effective decision-making, particularly when executing a shot. This study validates an innovative instrument, a training platform (TP), designed to measure and enhance decision-making in dual-task scenarios. The TP aims to improve visual-motor reactions in multitask environments that simulate real game conditions. Equipped with an LED panel, main circuitry, ball sensor, and targets, the TP challenges players to kick the ball in response to the illumination of the final LED array on the panel while hitting a designated target. The study evaluated three parameters: reaction time (RT), ball speed (BS) and accuracy. To validate the TP against a gold standard (GS), we conducted correlation analyses. The results exhibited very strong correlations for both RT (r = 0.997) and BS (r = 0.994). The mean differences between TP and GS measurements were 13 ± 15 ms for RT and 0.1 ± 0.5 km/h for BS. Bland-Altman plots revealed trend lines obtained by a simple linear regression of r = -0.507, p = 0.307 for RT and r = 0.134, p = 0.077 for BS. The TP effectively simulates game scenarios, offering advantages such as low-cost components, installation flexibility, test variability, instant feedback, and integration of physical and cognitive components of sports performance.